(untitled) (International Journal of Food and Nutritional Sciences, 2024)
This paper aims to explore the transformation of entertainment sources in Uttarakhand, specifically focusing on the period before and after the introduction of theatre. This paper delves into the historical evolution of entertainment sources in Uttarakhand. By examining the development of entertainment options in the region, the study aims to provide a comprehensive understanding of the changes that have occurred over time. The research focuses on the period leading up to the present day, tracing the roots of entertainment in Uttarakhand and exploring how it has evolved over the years. Through an analysis of historical records, archival material, and relevant literature, this study sheds light on the various forms of entertainment that have been prevalent in Uttarakhand, including traditional performances, folk arts, and community gatherings. The study also seeks to understand to the emergence of Uttarakhand regional cinema. By documenting the history of entertainment sources, this paper contributes to a deeper understanding of the cultural heritage and social dynamics of Uttarakhand.